Performance analysis of a fuel cell hybrid system subject to technological uncertainties. (1st December 2020) - Giugno, Andrea; Mantelli, Luca; Cuneo, Alessandra; Traverso, Alberto
Abstract: Nowadays research in energy field is focused on conversion technologies which could achieve higher efficiencies and lower environmental impact. In such a context, fuel cells in general and pressurized solid oxide fuel cell (SOFC) hybrid systems are attractive for their high electric efficiency, potential for cogeneration applications, low carbon emissions and high performance at part-load. The aim of this work is to perform the design under uncertainty of an innovative turbocharged hybrid system, where a turbocharger is used to pressurize the fuel cell, featuring better cost effectiveness than a microturbine-based hybrid system at small scales (<100kWe). In this study, a response surface of the plant steady-state performance is developed considering the main operating parameters (fuel cell area, stack current density and recuperator exchange surface) as factors to create the metamodel, taking into account the uncertainties related to the turbocharger efficiency and to the ohmic losses of the fuel cell stack. The optimal economic design of such a turbocharged hybrid system is then analysed at off-design conditions, to preliminary assess the operating costs and profitability within the Italian market scenario considering the variability of fuel and electricity prices. Finally, the impact of uncertainties both on plant performance and economics are discussed, showing that both payback period and internal rate of return present a significant variability, mostly due to the uncertainties related to the prices, showing that a proper evaluation of the evolution of the prices along the years should be performed for a proper economic feasibility analysis.